Revolutionizing Herbal Medicine: Exploring Nano Drug Delivery Systems - Pranav Kumar Prabhakar; Keshav Anand; Indu Bala; Rupendra Shakya; Harpreet Kaur Massaon; Abhilasha Suwalka; Bineesh CP; Anush N (Talenta Publisher, 2023)
Background: Traditional herbal medicine has been used for centuries and remains an important component of healthcare globally. However, the therapeutic effectiveness of many herbal remedies is often limited by issues such as poor bioavailability, low stability, and lack of targeted delivery. In recent years, the application of nanotechnology has emerged as a promising strategy to enhance the efficacy of herbal medicines. Objective: This review highlights recent advancements in nanotechnology-based delivery systems for herbal medicine and explores their potential applications in treating diseases such as cancer, cardiovascular conditions, neurodegenerative disorders, and inflammatory illnesses. Methods: Relevant literature from scientific databases published between 2015 and 2025 was reviewed and analyzed. Results: These systems improve solubility, protect compounds from degradation, prolong circulation time, and enable targeted delivery to specific tissues or cells. Moreover, nanocarriers can support the combination of multiple herbal ingredients, facilitating synergistic effects and personalized therapeutic approaches. Conclusion: The integration of nanotechnology and herbal medicine offers new possibilities in modern healthcare, although further research is required to address challenges in clinical translation, safety, and large-scale production. Collaboration among scientists, clinicians, and herbalists will be crucial in advancing this innovative field.